Prevalência de enteroparasitoses na população atendida em uma creche pública do Rio Grande, RS, e comparação de métodos de diagnósticos para giardíase - Berne, Ana Cristina (2007)
The enteroparasitosis remains as an important public health problem in children in the Brazil, showing variable prevalence, according to the State and evaluated population. Studies with day-care center children are scarce, however, already knows that the exposure of the children in these places increased the susceptibility to parasitosis. Among the parasitosis the protozoary Giardia lamblia is responsible for severe diarrhea cases in children and the routine diagnosis methods presents many false negative results. The aim of this study was investigate the enteroparasitosis prevalence in children from a day-care public center of Rio Grande county, Rio Grande do Sul State and compare diagnosis techniques in samples of their fecal material to Giardia lamblia , the ELISA immunoassay and the centrifugal-sedimentation methods. 165 fecal samples where evaluated and processed by centrifugal-sedimentation and centrifugal-flotation methods, stained by trichromium and Kinyoun after the concentration by centrifugal-sedimentation. The general prevalence of enteroparasitosis was 64,2% (106/165). The most prevalent nematods species founded was Trichuris trichiura (24,2%) and Ascaris lumbricoides (22,4%) and the the most prevalent protozoary specie was Giardia lamblia (30,3%). The presence of opportunists coccids where also registered Cryptosporidium spp. (2,4%) and Isospora belli (0,6%). Among the positives 56,6% (60 samples) showed simple infection and 43,4% (46 samples) showed associated infection. The presence of non pathogenic protozoary like Entamoeba coli (15,2%), Endolimax nana (3,6%) and Enteromonas hominis (4,8%), indicated environmental fecal source contamination. The higher prevalence of nematods and protozoary in the studied population suggests the necessity of implementation of educational measures to prevent these enteroparasites. In the evaluation of comparative diagnosis of G. lamblia a higher positivity was verified in the ELISA technique 57% (90/158), followed by the centrifugal-sedimentation method 27,8% (44/158). The obtained results in this study suggests that is higher the prevalence of nematods and protozoary in the evaluated children and the ELISA technique to detect antigen in fecal sample showed higher efficiency to giardiasis diagnosis.